Analisis Keterbacaan Buku Bahasa Arab Berbasis Karakter - Triya Fadhilah Dhianty Putri; Rinaldi Supriadi; Mohamad Zaka Al Farisi (LP2M IAIN Sultan Amai Gorontalo, 2023)
One strategy in determining the success of learning is textbooks or schoolbooks. However, we often find books that are not up to standard and impact student understanding. Understanding the book’s contents is so closely related to the ease or difficulty of the material, or is called readability that the contents of the text need to be evaluated and adjusted to the competence of students so that learning objectives are achieved not only increase in the academic field but also students' moral behavior. This research aims to describe the readability of discourse based on the fog index formula statistically and compiled descriptively and then to analyze the character values based on the profile of Pancasila students published by the Standards, Curriculum, and Education Assessment Agency (BSKAP). This research was designed using a qualitative descriptive method with a content analysis model. The results of the study readability level in this book are 2.44, which means that this value belongs to the very easy-to-read category. This book fulfills the character values of the Pancasila students’ profile; namely: (1) having faith, fearing God Almighty, and having noble characters, (2) global diversity, (3) working together, (4) being independent, (5) critical reasoning, and (6) being creative.